Skrining Aktivitas Antibakteri Ekstrak Etanol Daun Terhadap Salmonella Typhi Resisten Kloramfenikol - Trisharyanti, Ika (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2017)
Typhoid fever is an infectious disease caused by Salmonella typhi, antibiotic chloramphenicol can be use to treatment, but S. typhi resistant with antibiotic choramphenicol so need to alternative treatment. The purpose of this study was to determine the antibacterial activity of ethanol extract of ten leaves against Salmonella typhi, and knowing the compounds contained in extracts of leaves that have the best antibacterial activity. The leaves was extracted withÂ  ethanol 96% by maceration method. Screening antibacterial activity used disk diffusion method with 10% extract concentration. The best antibacterial activity was determined Minimum Inhibitory Concentration and Minimum Bactericidal Concentration used liquid dilution method, identification test of compounds with thin-layer chromatograpy (TLC), and bioautografi test. There were six extracts had antibacterial activity against S. Typhi, Phaleria macrocarpa leaves, Acalypha siamensis leaves, cherry leaves, clove leaves, tea leaves, and Eugenia polyantha leaves. Minimum Bactericidal Concentration from clove leaf extract was 2,5%. The results of identification by TLC compounds were alkaloids, phenolics, flavonoids, terpenoids, triterpenoids, and saponins. Based on bioautografi test,Â  phenolic can inhibit the growth of Salmonella typhi.